Two courses of four weekly infusions of rituximab with or without interferon-α2a: final results from a randomized phase III study in symptomatic indolent B-cell lymphomas. Issue 9 (2nd September 2015) - Kimby, Eva; Östenstad, Björn; Brown, Peter; Hagberg, Hans; Erlanson, Martin; Holte, Harald; Linden, Ola; Johansson, Ann-Sofie; Ahlgren, Tomas; Wader, Karin; Wahlin, Björn Engelbrekt; Delabie, Jan; et al.
Abstract : Patients with advanced CD20 + indolent lymphoma, requiring therapy, were randomized to rituximab (four weekly infusions of 375 mg/m 2 ) or to rituximab combined with 5 weeks of interferon-α2a (IFN-α2a) (3–4.5 MIU daily) as priming. Responding patients were eligible for a second cycle with the same allocated treatment. In total, 156 patients were randomized to rituximab and 157 to rituximab + IFN-α2a. In the intention-to treat (ITT) population, 244 patients (78%) responded to cycle 1. After a second cycle the complete remission/complete remission unconfirmed (CR/CRu) rate was 41% with the combination versus 24% with monotherapy ( p = 0.005). The median time to treatment failure (primary endpoint) in ITT patients was 28 vs. 21.5 months, respectively ( p = 0.302). After a long median follow-up (61 months), 33% (42% of patients responding to cycle 1) were still failure-free with an overall survival rate of 88% and with no difference between the treatment groups. The trial was registered at ClinicalTrials.gov Identifier: NCT01609010.